Fabrication of Polypropylene (PP)/Poly Trimethylene Terephthalate (PTT)/Nanoclay Nanocomposite Fibers with Tailored Properties. Issue 9 (2nd September 2019) - Zargar, Mohammad Reza Habibolah; Shoushtari, Ahmad Mousavi
Abstract: The main aim of this study was to deal with one of the major drawbacks of polypropylene (PP) fibers, i.e., low resiliency and low dyeability, by incorporating polytrimethylene terephthalate (PTT) fibrils, as a dispersed material, and organoclay, as a nano-filler, into the PP polymer matrix. The presence of 10 wt% of PTT and 0.5–1 wt% organoclay in the PP nanocomposite fibers led to an approximately 18.5% and 45.5% increase in the resilience behavior and dye uptake, respectively, compared to pure PP fibers, without using highly toxic carriers. The lowest mean diameter of the nano-fibrils was 75 nm for the hot drawn nanocomposite fiber samples as measured by scanning electron microscopy (SEM). The results of DSC indicated that the presence of both PTT and organoclay significantly influenced the crystallinity of the PP which also confirmed their nucleating effects in the nanocomposite fiber.